Vulnerability of aquaculture-related livelihoods to changing climate at the global scale - Neil Handisyde; Trevor C Telfer; Lindsay G Ross (Wiley Online Library, 2025)
There is now a strong consensus that during the 20th century, and especially during recent decades, the earth has experienced a significant warming trend with projections suggesting additional further warming during the 21st century. Associated with this warming trend are changes in climate that are expected to show substantial spatial variability across the earth’s surface. Globally, fish production has continued to increase during recent years at a rate exceeding that of human population growth. However, the contribution from capture fisheries has remained largely static since the late 1980s with the increase in production being accounted for by dramatic growth in the aquaculture sector. In this study, the distribution of vulnerability of aquaculture-related livelihoods to climate change was assessed at the global scale based on the concept of vulnerability as a function of sensitivity to climate change, exposure to climate change and adaptive capacity. Use was made of national-level statistics along with gridded climate and population data. Climate change scenarios were supplied using the MAGICC/SCENGEN climate modelling tools. Analysis was conducted for aquaculture in freshwater, brackish and marine environments with outputs represented as a series of raster images. A number of Asian countries (Vietnam, Bangladesh, Laos and China) were indicated as most vulnerable to impacts on freshwater production. Vietnam, Thailand, Egypt and Ecuador stood out in terms of brackish water production. Norway and Chile were considered most vulnerable to impacts on marine production while a number of Asian countries (China, Vietnam and the Philippines) also ranked highly.